I. M. LYTVYN: INTERPRETIVE APPROACH TO THE FICTION TRANSLATION (based on the Ukrainian translation of the detective story «The Absence of Mr. Glass» by Gilbert Chesterton) - LYTVYN, I. M. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. The article deals with the topical issue of contemporary translation studies – the interpretive approach to the process of fiction translation. Purpose. The purpose of our article is to analyze the interpretive approach to the process of fiction translation in combination with the purpose, the strategy of translation, transformational potential of the target language and creativity of the translator. The research is conducted on the basis of the detective story «The Absence of Mr. Glass» by Gilbert Chesterton and its modern Ukrainian translation. The translator is Ievgen Tarnavskyi. The interpretive theory of translation is characterized. Danica Seleskovitch and Marianne Lederer have created this theory as the rational theoretical model that explains the process of translation as a communicative act. The interpretive theory focuses on the main phases of this process: perception, understanding of the source text, deverbalization and its usual reformulation on the basis of translator’s conceptual understanding. The theory is innovative in defining the sense as a conscious mental representation which is defined by the influence of linguistic meanings and extralinguistic knowledge of the recipients of the text. Results. The interpretive approach is usually combined with the ethnocultural strategy of translation (the term of Olena Selivanova) (eng. domesticating strategies is the term of Lawrence Venuti). The translator of Gilbert Chesterton’s detective story «The Absence of Mr. Glass» chooses the ethnocultural strategy. He focuses on the modern Ukrainian readers and adapts the translated text to the Ukrainian culture. Originality. The interpretive approach to literary translation is demonstrated. Conclusions. The interpretative approach to the process of translation in combination with the ethnocultural strategy and creativity of the translator Ievgen Tarnavskyi has adapted the humorous and paradoxical short story «The Absence of Mr. Glass» to the Ukrainian readers of the 21st century. The research of the interpretive approach to the process of audiovisual translation is promising. It can be used in the further development of the interpretive theory as a rational theoretical model that explains the process of translation.